New tools to evaluate plastic ingestion by northern fulmars applied to North Sea monitoring data 2002–2018 - van Franeker, Jan A.; Kühn, Susanne; Anker-Nilssen, Tycho; Edwards, Ewan W.J.; Gallien, Fabrice; Guse, Nils; Kakkonen, Jenni E.; Mallory, Mark L.; Miles, Will; Olsen, Kåre Olav; Pedersen, John; Provencher, Jennifer; et al. (Marine Pollution Bulletin, 2021)
Monitoring plastic in stomachs of beached northern fulmars for OSPAR's Ecological Quality Objectives (EcoQOs) has been incorporated into the European Marine Strategy Framework Directive (MSFD). This paper aims to provide the appropriate tools to interpret the monitoring results. MSFD requires a data-derived threshold value (Fulmar-TV) representing ‘Good Environmental Status’. Such Fulmar-TV was calculated from near-pristine Canadian Arctic data where 10.06% of fulmars exceeded the level of 0.1 g ingested plastic. This Fulmar-TV is almost identical to the earlier OSPAR EcoQO, arbitrarily set at 10%. The MSFD approach was evaluated for 2661 North Sea fulmars in 2002–2018. Between 2014 and 2018, 51% of 393 fulmars exceeded 0.1 g plastic, significantly above the proposed Fulmar-TV. Linear regression of individual ingested plastic mass over the 2009–2018 period indicates a significant decrease. Over the longer term 2002–2018, logistic regression of annual EcoQ% shows a significant decline and predicts compliance with the Fulmar-TV by 2054.